EVALUASI IMPLEMENTASI PELAYANAN KONSELING OBAT DI APOTEK KOTA YOGYAKARTA - farida baroroh; endang darmawan (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2016)
Therefore, it is important to give counseling for patients and their family. This study is to evaluate the counseling service implementation at several pharmacy in Yogyakarta Indonesia. This study was a cross-sectional design. The result showed that the implementation counseling service at pharmacy was 59,00% of 96,00% patients who required counseling service. The several pharmacy patient were out-patient who responsible to their therapeutical management. There was 55,93% patients experienced that the room for counseling service was comfortable. So, the communication aspects of counseling service at pharmacy in Yogyakarta had been well conducted. Based on the communication technique, the pharmacist communicated with body language such as practicing how to use the drug in counseling services was 64.41%. In conlusion, the implementation counseling service at pharmacy in Yogyakarta Indonesia was 59,00% of 96,00% patients who required counseling service. A number of 94.83% of patients stated that pharmacists use an understandable language in counseling services. It can be concluded that although only 58.59% of respondents who had received counseling but the desire to get counseling services of pharmacy in Yogyakarta is very high, reaching 95.96% of respondents